These Silent Woods - Grant, Kimi Cunningham (New York : St. Martin's Paperbacks, 2021)
"A father and daughter living in the remote Appalachian mountains must reckon with the ghosts of their past in Kimi Cunningham Grants These Silent Woods, a mesmerizing novel of suspense. No electricity, no family, no connection to the outside world. For eight years, Cooper and his young daughter, Finch, have lived in isolation in a remote cabin in the northern Appalachian woods. And thats exactly the way Cooper wants it, because hes got a lot to hide. Finch has been raised on the books filling the cabins shelves and the beautiful but brutal code of life in the wilderness. But shes starting to push back against the sheltered life Cooper has created for her-and hes still haunted by the painful truth of what it took to get them there. The only people who know they exist are Scotland, an overly friendly hermit with murky intentions, and Coopers old friend, Jake, who visits each winter to bring them food and supplies. But this year, Jake doesnt show up, setting off an irreversible chain of events that reveals just how precarious their situation really is. Suddenly, the boundaries of their safe haven have blurred- and when a stranger wanders into their woods, Finchs growing obsession with her could put them all in danger. When a shocking disappearance threatens to upend the only life Finch has ever known, Cooper is forced to decide whether to keep hiding-or finally face the sins of his past. Vividly atmospheric and masterfully tense, These Silent Woods is a poignant story of survival, sacrifice, and how far a father will go when faced with losing it all"--
Keywords: Fathers and daughters -- Fiction; Survival -- Fiction; Appalachian Mountains -- Fiction; Fiction